Resveratrol’s Anti-Cancer Effects through the Modulation of Tumor Glucose Metabolism - Aranka Brockmueller (11064675) (2021)
Tumor cells develop several metabolic reprogramming strategies, such as increased glucose uptake and utilization via aerobic glycolysis and fermentation of glucose to lactate; these lead to a low pH environment in which the cancer cells thrive and evade apoptosis. These characteristics of tumor cells are known as the Warburg effect. Adaptive metabolic alterations in cancer cells can be attributed to mutations in key metabolic enzymes and transcription factors. The features of the Warburg phenotype may serve as promising markers for the early detection and treatment of tumors. Besides, the glycolytic process of tumors is reversible and could represent a therapeutic target. So-called mono-target therapies are often unsafe and ineffective, and have a high prevalence of recurrence. Their success is hindered by the ability of tumor cells to simultaneously develop multiple chemoresistance pathways. Therefore, agents that modify several cellular targets, such as energy restriction to target tumor cells specifically, have therapeutic potential. Resveratrol, a natural active polyphenol found in grapes and red wine and used in many traditional medicines, is known for its ability to target multiple components of signaling pathways in tumors, leading to the suppression of cell proliferation, activation of apoptosis, and regression in tumor growth. Here, we describe current knowledge on the various mechanisms by which resveratrol modulates glucose metabolism, its potential as an imitator of caloric restriction, and its therapeutic capacity in tumors. Other Information Published in: Cancers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/cancers13020188